eKhairat system - Rabiatul Najwa, Mat Ezam (2019)
EKhairat system is a system that will be used by most organizations in Malaysia. This system is a system for storing all user information. There are three reasons why this happened. First, user information is easy to lose. Second is wastage in paper usage and reduces storage of consumer information. The main objective of this project is to facilitate both users and system administrators to store user information who wish to engage in monthly deaths expenses. The system also focuses on how the prophecy uses the eKhairat system in the daily life of consumers who wish to engage in a monthly mortality payment that can bring benefits and impact to the user. This study proposes the use of information storage systems through online.